Comparison of embolization strategies for mixed plexiform and fistulous brain arteriovenous malformations: a computational model analysis of theoretical risks of nidus rupture. (10th December 2021) - Jain, Mika S; Telischak, Nicholas A; Heit, Jeremy J; Do, Huy M; Massoud, Tarik F
Abstract : Background: High-flow fistulas related to plexiform nidi are found in 40% of large brain arteriovenous malformations (AVMs). Endovascular occlusion of intranidal fistulas before plexiform components is empirically considered safe, but potential ensuing dangerous re-routing of flow through plexiform vessels may in theory raise their rupture risk. It remains unclear whether it is safer to embolize plexiform or fistulous vessels initially. We used a novel biomathematical AVM model to compare theoretical hemodynamic changes and rupture risks on sequential embolizations of both types of nidus vessels. Methods: We computationally modeled a theoretical AVM as an electrical circuit containing a nidus consisting of a massive stochastic network ensemble comprising 1000 vessels. We sampled and individually simulated 10 000 different nidus morphologies with a fistula angioarchitecturally isolated from its adjacent plexiform nidus. We used network analysis to calculate mean intravascular pressure (Pmean ) and flow rate within each nidus vessel; and Monte Carlo analysis to assess overall risks of nidus rupture when simulating sequential occlusions of vessel types in all 10 000 nidi. Results: We consistently observed lower nidus rupture risks with initial fistula occlusion in different network morphologies. Intranidal fistula occlusion simultaneously reduced Pmean and flow rate within draining veins. Conclusions: Initial occlusion of AVM fistulas theoretically reduces downstream draining vessel hypertension and lowers the risk of rupture of an adjoining plexiform nidus component. This mitigates the theoretical concern that fistula occlusion may cause dangerous redistribution of hemodynamic forces into plexiform nidus vessels, and supports a clinical strategy favoring AVM fistula occlusion before plexiform nidus embolization.